O cotidiano de trabalho do assistente social na Casa de Apoio UNIFESP/CACAU - Rosa, Lara Terezinha Rodrigues (2016)
This dissertation discusses and deeper reflection on the everyday reality of users Treatment Outside Domicilio-TFD and Support House UNIFESP/CACAU. The built reflection web over the four chapters that make up this dissertation is the result of an intense dialogue with the Marxist theoretical framework and the research participants, considering that we have chosen the qualitative methodology, through the mediation of oral history that from the narratives brought by patients and caregivers of the House of Support, we grasp the meanings of livings and conviviality during the period of medical treatment outside of the household. Participants of this research were intentionally chosen, forming a universe of six speakers with experience intensely lived under the Support House and TFD. In this sense, in chapter I present the theoretical foundations that have sustained our methodological construction to go findado field in ethical perspective. In Chapter II, in brief statements we contextualize the Brazilian socio-historical formation, as well as the trajectory Health Policy in Brazil, discussing elements related to the SUS and TFD. Finally, in Chapters III and IV, we deepen the reflection on the daily work of the social worker in Support House and the meaning of home support in the life trajectories of users of this service and treatment outside of domicile. Closer to the everyday reality of survey participants was a challenging and very important process because we know the area of ethical and political mediations that, despite the many daily challenges of reality treatment outside household and hosting Support House points out ways and possibilities of reflections aimed at ensuring the quality of health care and the emancipatory empowerment in the struggle for Saude Publica universal, full and equal access